Approximate method for fast retrieval of particle size distribution in spectral extinction technique - Wang, Li; Sun, Xiaogang; Li, Feng (Photonics Letters of Poland, 2011)
Generalized eikonal approximation (GEA) method, used as an alternative to the rigorous Mie theory in this paper, is introduced for retrieval of the particle size distribution (PSD) in the independent model. To compute the extinction efficiency accurately, the combination of GEA method and Mie theory is adopted, which can not only extend the applicable range of the approximation method but also improve the speed of the whole retrieval. Both simulations and experimental results show the method can be successfully applied to retrieval of PSD when the refractive index is within the validity range. By using this method, we find the complexity and computation time of the retrieval are significantly reduced, and the memory resources can also be saved effectively. Thus all of these factors make the method more suitable for realization of on-line particle sizing. Full Text: PDF References C.F. Bohren, D.R. Huffman, Absorption and Scattering of Light by Small Particles (Wiley, 1998)[CrossRef] H.Y. Zuo et al., "Technique to improve the accuracy of the retrieval of aerosol size-distribution", Opt. Lett. 35, 1380 (2010)[CrossRef] M.Z. Li, D. Wilkinson, "Particle size distribution determination from spectral extinction using evolutionary programming", Chem. Eng. Sci. 56, 3045 (2001)[CrossRef] X.Z. Li et al., "Geometrical-optics approximation of forward scattering by gradient-index spheres", Appl. Opt. 46, 5241 (2007)[CrossRef] X.G. Sun, H. Tang, J.M. Dai, "Retrieval of particle size distribution in the dependent model using the moment method", Opt. Exp. 15, 11507 (2007)[CrossRef] S.K. Sharma, D.J. Somerford, Light Scattering by Optically Soft Particles: Theory and Applications (Springer-Praxis, 2006) T.W. Chen, "High energy light scattering in the generalized eikonal approximation", Appl. Opt. 28, 4096 (1989)[CrossRef] M. Kandlikar, G. Ramachandran, "Inverse methods for analysing aerosol spectrometer measurements: a critical review", J. Aerosol Sci. 30, 413 (1999)[CrossRef]